Digital Marketing Sebagai Sarana Pemasaran Produk UMKM Tahu Di Buantan Lestari - Alia, Filma; Situmeang, Apriyani Rosita; Saputra, Eko (Journal of Community Engagement Research for Sustainability, 2024)
Loka Karya Digital Marketing as a Means of Marketing MSME Tofu Products the purpose is to find out the impact of digital marketing on the sales of MSME products, by comparing these MSMEs before and after using digital marketing marketing as a means of product promotion and sales. The marketing target of tofu products includes MSMEs, markets, and communities in Buantan Lestari Village, Bunga Raya. Based on the result of qualitative research with interview and observation techniques as well as the data that has been collected by the author, it can be concluded that digital marketing has a huge influence on product marketing because it can increase the sales volume and also increase the profits for MSME entrepreneurs.